ANALISIS SISTEM PENGENDALIAN INTERN DALAM PEMUNGUTAN RETRIBUSI TERMINAL ANGKUTAN SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN ENDE - Mochdar, Kartika Saridewi; Marselina, Apriana; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2023)
This study aims to determine how the implementation of the internal control system in collecting transportation terminal levies in Ende district as a source of local original income (PAD) has been running. The type of research used in this study is qualitative descriptive research. The location of the research was carried out at the office of the Transportation Office located on Jalan Ahmad Yani No.14 Ende Regency. The type of data used in this study is qualitative data obtained from the object under study using dokementation, observation, interview and literature study techniques. The qualitative data obtained are data on internal control in collecting regional levies in the form of explanations and descriptions obtained from the objects studied and written documents at the Ende Regency Transportation Office. In this study using primary data and secondary data. The design used to analyze this study is a descriptive method. The Internal Control System implemented by the Ende Regency Transportation Office in collecting terminal levies has not been in accordance with the government's internal control system Number 25 of 2018 because it does not use the existing/installed Control Evaluation and Revision of policies and procedures.